2018
DOI: 10.2174/1568009618666180308104646
|View full text |Cite
|
Sign up to set email alerts
|

Parp Inhibitors for the Treatment of Ovarian Cancer

Abstract: The standard of treatment for advanced ovarian cancer is represented by optimal surgical debulking preceded or followed by chemotherapeutic regimens including taxanes and platinum agents, possibly associated with bevacizumab and/or intraperitoneal therapy. Despite this comprehensive treatment strategy, almost 75% of patients relapse or progress and are therefore candidates for a second-line treatment, showing, at this point, less chemo-sensitivity and worse prognosis. An interesting approach to improve outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Poly-(ADP) ribose polymerase inhibitors (PARPi) have been used as anticancer agents since the early 2000s (McCabe et al, 2006), and the first PARPi, olaparib, was approved for BRCA-mutated ovarian cancer in 2014 (Kim et al, 2015). Approval of these drugs was first given for the treatment of breast and ovarian cancers, and studies found that this therapy regimen was most effective in cells that carry functional defects in DNA DSB pathways, most notably in BRCA-mutated cells (Cortesi et al, 2018;Ghiringhelli et al, 2016;Lin et al, 2014;Lord and Ashworth, 2017;Mittica et al, 2018;Sunada et al, 2018). Recent studies ascribed this synthetic lethality phenotype to the loss of PARP activity at replication forks, suggesting that PARP inhibition promotes rapid fork progression, leading to increased genome instability that the cell cannot overcome when HR defects are also present (Maya-Mendoza et al, 2018).…”
Section: Parp Inhibitorsmentioning
confidence: 99%
“…Poly-(ADP) ribose polymerase inhibitors (PARPi) have been used as anticancer agents since the early 2000s (McCabe et al, 2006), and the first PARPi, olaparib, was approved for BRCA-mutated ovarian cancer in 2014 (Kim et al, 2015). Approval of these drugs was first given for the treatment of breast and ovarian cancers, and studies found that this therapy regimen was most effective in cells that carry functional defects in DNA DSB pathways, most notably in BRCA-mutated cells (Cortesi et al, 2018;Ghiringhelli et al, 2016;Lin et al, 2014;Lord and Ashworth, 2017;Mittica et al, 2018;Sunada et al, 2018). Recent studies ascribed this synthetic lethality phenotype to the loss of PARP activity at replication forks, suggesting that PARP inhibition promotes rapid fork progression, leading to increased genome instability that the cell cannot overcome when HR defects are also present (Maya-Mendoza et al, 2018).…”
Section: Parp Inhibitorsmentioning
confidence: 99%
“…PARP inhibitors such as Olaparib are currently a novel targeted drugs for the treatment of BRCA-mutant ovarian cancer. The use of an HR repair defect mechanism leads to cell cycle arrest and apoptosis 30. Inhibition via gene targeting inhibition in BRCA-proficient tumors in combination with Olaparib could result in a synergistic increase in DNA damage and G2/M cell-cycle checkpoint defects, which may allowed cells to enter mitosis despite the accumulation of DNA damage, ultimately causing mitotic catastrophe 31.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, another two PARP inhibitors, niraparib [ 16 ], and rucaparib [ 17 ] have been granted approval in the maintenance setting of ovarian cancer, regardless of BRCA1/2 status. Furthermore, both olaparib [ 18 ] and talazoparib [ 19 ] are approved in human epidermal growth factor receptor 2 (HER2)-negative, g BRCA1/2 -mutation-associated metastatic breast cancer [ 20 ]. Finally, several trials of olaparib in patients with g BRCA1/2 mutations identified responders beyond ovarian or breast cancer patients, suggesting that other HRR-defective tumors could be suitable for PARPi treatment [ 14 ].…”
Section: Introductionmentioning
confidence: 99%